Transition from negative dielectric constant to positive dielectric constant of MXene by ZnO nanoparticles produced by Fytronix hydrothermal method - Demirelli, Kadir; Ercan, Cemile; Dere, Aysegul; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2025)
ZnO nanoparticles and MXene/ZnO nanocomposites were synthesized by hydrothermal method. The MXene/ ZnO nanocomposites were prepared in ZnO matrix with different compositions. All composite materials were synthesized in powder form. The structural properties of the composites were analyzed by Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray Analyser (EDX), X-ray diffraction (XRD) spectroscopy. The SEM-EDX analysis confirm that the ZnO nanoparticles has an hexagonal wurtzite structure. The dielectric constant of pure MXene was observed to be negative and is decreased with increasing temperature, the dielectric constant and dielectric loss of MXene/ZnO nanocomposite is increased with increasing temperature. The dielectric behaviour of MXene, a metamaterial, was converted from negative dielectric behaviour to positive dielectric property by the addition of ZnO. The metamaterial MXene with negative dielectric constant was discussed in detail. The dielectric properties of MXene were improved by the addition of ZnO nanoparticles and shown to be highly temperature and voltage dependent. The anomalous dielectric behaviours of MXene/ZnO nanocomposite were observed in the frequency range of 7.5 MHz-13.0 MHz. The DC and AC conductivities of the composites with different concentrations of MXene and MXene/ZnO nanocomposites have been investigated as a function of frequency, temperature and voltage. Dielectric characteristics of the samples have been investigated using the capacitance and admittance spectoscopy. The relaxation process of the MXene0.30/ZnO nanocomposite was analyzed between 5 MHz and 10 MHz above 100 degrees C. It is evaluated that negative dielectric constant of MXene is converted to the positive dielectric constant by addition of ZnO nanoparticles.
Keywords: MXene; Zinc oxide; Nanocomposite; Negative dielectric constant; Cole-Cole; Metamaterial